Financing Sustainability: Critical Issues with East Asian Experiences. Edited by Rajah Rasiah, Gopi Krishnan & Azleen Osman Rani. Universiti Malaya Press, 2022. - Rajaseharan, Arjun (AEI Insights, 2023)
Book